Assessing the digital competence and its influencing factors among foreign language teachers in Chinese universities - Hong Lei; Zhanhao Jiang (Humanities & Social Sciences Communications)
Abstract This study empirically investigates the current status of the digital competence of 582 foreign language teachers in universities across the eastern, central, and western regions in China. The results indicate that the questionnaire based on the Ministry of Education’s Digital Literacy of Teachers Standards has high reliability and validity. The survey findings show that teachers generally rate their digital competence positively at an intermediate level, with most expressing a willingness to actively learn and use digital technologies to promote professional development. However, there is a need to improve teachers’ ability to use digital technologies in teaching activities, particularly in academic assessment. The study also reveals significant differences in digital competence levels among teachers with different years of teaching experience and from different regions. As teaching experience increases, digital competence levels decrease; teachers in the eastern region have significantly higher digital competence than those in the central and western regions. Moreover, the surveyed teachers identify several key factors influencing their digital competence: targeted training, personal willingness to learn, and support from policies and resources. Overall, this study provides policymakers with a comprehensive overview of the digital competence among higher education foreign language teachers in China, and offers these teachers a useful tool to assess their digital competence.